Should Breastfeeding Be Interrupted after Radiological Imaging Examinations? Evidence and Clinical Applications - Şeyma Karatekin; Ebru Şenol; Nalan Karabayır (MDPI AG, 2024)
Purpose: Breastfeeding provides optimal growth and development for infants. Lactating mothers may have challenges maintaining breastfeeding, and one of those challenges is being falsely advised to interrupt breastfeeding following radiologic studies. The aim of this study was to evaluate the knowledge, attitudes and experiences of healthcare professionals regarding breastfeeding after radiological imaging studies on lactating mothers. Method: In this cross-sectional study, an online survey consisting of 29 semi-structured questions was delivered to radiology technicians and physicians in radiology and pediatrics via social media. Mixed methods were used to analyze responses descriptively. Results: Of the 404 participants, 39% (n = 158) were radiology technicians, 31% (n = 125) were pediatricians, 11% (n = 46) were radiologists, 10% (n = 41) were pediatric residents and 8% (n = 34) were radiology residents. Of all healthcare professionals, 91% reported that breastfeeding does not need to be interrupted after ultrasound, 75% X-ray, 56% mammography, 62% non-contrast CT, 18% contrast-enhanced CT, 93% non-contrast MRI and 23% contrast-enhanced MRI. Interruption of breastfeeding was recommended more frequently after contrast-enhanced imaging studies (p < 0.01). After contrast-enhanced CT, 54% of participants recommended pumping and dumping for <24 h and 25% for 24-48 h; after contrast-enhanced MRI, these rates were found to be 57% and 20%, respectively. Of the healthcare professionals, 63% reported that their knowledge about management of breastfeeding after radiological studies was not sufficient. Conclusions: Situations requiring the interruption of breastfeeding after radiological studies are rare. However, recommendations in clinical practice vary in our country. Increasing the awareness and knowledge of healthcare professionals will prevent breastfeeding from being negatively affected.